2020
DOI: 10.1055/a-1160-9902
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamin D on Metabolic Profiles in Women with Polycystic Ovary Syndrome: A Systematic Review

Abstract: This systematic review aims to evaluate all epidemiological evidence in the literature linking the effect of vitamin D supplementation to metabolic and hormonal functions in women with polycystic ovary syndrome. The literature search was performed with two databases, namely Medline/PubMed and Web of Science, until 20 May 2019 for both observational and experimental studies concerning relationships between vitami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In line with these results multiple recent studies documented that oral VD supplemental therapy significantly decreased serum fasting blood glucose and serum insulin, TC, TG and VLDL-C, thus exerting favorable effects on glucose metabolism and lipid metabolism, especially in VD deficient PCOS women [30,31,32] . Furthermore, other recent studies documented the favorable effect of VD supplemental therapy on patients' lipid profile, oxidative stress and inflammatory status [33,34,35] and additionally reported improvement of endometrial receptivity [33] , hirsutism [34] and ovulation rate in subfertile women with PCOS undergoing induction of ovulation [35] .…”
Section: Discussionmentioning
confidence: 86%
“…In line with these results multiple recent studies documented that oral VD supplemental therapy significantly decreased serum fasting blood glucose and serum insulin, TC, TG and VLDL-C, thus exerting favorable effects on glucose metabolism and lipid metabolism, especially in VD deficient PCOS women [30,31,32] . Furthermore, other recent studies documented the favorable effect of VD supplemental therapy on patients' lipid profile, oxidative stress and inflammatory status [33,34,35] and additionally reported improvement of endometrial receptivity [33] , hirsutism [34] and ovulation rate in subfertile women with PCOS undergoing induction of ovulation [35] .…”
Section: Discussionmentioning
confidence: 86%
“…However, there are also interventional studies, which provided divergent results [34][35][36]. Wamberg et al found no treatment effect of high-dose vitamin D (7000 IU/day) for 26 weeks on blood pressure, lipid profile, and HOMA-IR in obese adults [35].…”
Section: Discussionmentioning
confidence: 99%
“…Wamberg et al found no treatment effect of high-dose vitamin D (7000 IU/day) for 26 weeks on blood pressure, lipid profile, and HOMA-IR in obese adults [35]. A recent meta-analysis in 2020 summarized that the use of vitamin D supplementation did not influence glucose parameters but improved other metabolic profiles in participants with polycystic ovary syndrome, especially when combined with calcium [36]. Taken together, the inconsistent results from the available evidence may attribute to the fact that most of the studies were short in duration, had different baseline 25(OH)D and metabolic profile, or used post-hoc analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Vit.D and calcium therapy normalize the menstrual cycles in PCOS 9 . Further, studies have shown the therapeutic effects of Vit.D on hormone imbalances and metabolic disorder in women with PCOS, such as hyperandrogenism, hyperlipemia and insulin resistance, and high dose of Vit.D was recommended [10][11][12] . These ndings support the hypothesis that Vit.D de ciency may contribute to the development of PCOS, and Vit.D may be a feasible treatment for PCOS.…”
Section: Introductionmentioning
confidence: 99%